Validity of the Role-Playing Game (RPG) Educational Game Thermochemical Concepts as an Independent Learning Media - Firdaus, Hafiz; Muna, Khairiatul; Bahit, Muhammad (International Journal of STEM Education for Sustainability, 2025)
Technological advances can be used to simplify the learning process. This use includes the use of games as a product of technological progress. Games make the concepts presented interesting. One type of game that can be used is a role-playing game (RPG). RPG games are games that focus on story and character development. Students often lack the motivation to learn. Apart from that, students also have difficulty learning thermochemical concepts. This study aimed to describe the validation of thermochemical concepts RPG game learning media based on the assessment of material experts and media experts. Assessment is carried out using a validation sheet. This study used a research and development (RD) method. Then the results obtained are divided into very valid, valid, quite valid, invalid, and very invalid. Based on the material expert's assessment, the thermochemical concepts RPG game learning media was rated very valid (89%), and based on the media expert's assessment, it was rated as valid (80%), so the learning media developed could be implemented.